Ethics, One Health approaches, and SDGs: conference lessons for an emerging field - Lerner, Henrik; Nordquist, Rebecca E.; Lederman, Zohar; Keyel, Jared; Nickel, Patricia Mooney; Berg, Charlotte (Frontiers in Public Health, 2024)
One Health ethics is an emerging field that has gained traction since its origin in approximately 2015. This article builds upon the insights shared during a panel discussion on One Health, Sustainable Development Goals (SDGs), and ethical conflicts at the 28th Annual International Sustainable Development Research Society Conference. The conference, themed Sustainable Development and Courage: Culture, Art, and Human Rights, aimed to advance and expand recent knowledge in the field. Key themes discussed during the conference panel included interdisciplinarity and multidisciplinary, risk, resilience, wicked problems with no readily available solutions, and praxis. A conclusion is that ethics should become more prominent within One Health discussions. Four aspects emerged from this discussion: (1) Ethics is needed to solve wicked problems within One Health approaches. (2) Aspects of multi-, inter-, and transdisciplinarity need to be considered together with their implications for ethics. (3) Two crucial concepts, risk and resilience, need to be addressed. (4) Ethical decision models are called for and need to be developed.